2008
DOI: 10.1021/bi800711t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PIP2 Binding on the Membrane Docking Geometry of PKCα C2 Domain: An EPR Site-Directed Spin-Labeling and Relaxation Study

Abstract: Protein kinase C isoform alpha (PKCα) is a ubiquitous, conventional PKC enzyme that possesses a conserved C2 domain. Upon activation by cytoplasmic Ca2+ ions, the C2 domain specifically binds to the plasma membrane inner leaflet where it recognizes the target lipids phosphatidylserine (PS) and phosphatidylinositol-4,5-bisphosphate (PIP2). The membrane penetration depth and docking angle of the membrane-associated C2 domain is not well understood. The present study employs EPR site-directed spin labeling and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(102 citation statements)
references
References 53 publications
8
94
0
Order By: Relevance
“…Given the close proximity of the lysine-rich cluster and the CBR, these results are compatible with a parallel orientation model (Fig. 6F) in which these two motifs would interact with a vesicle representing the plasma membrane, leaving the bottom face free to interact in trans with another lipid vesicle (19,(47)(48)(49)(50)(51). How these two C2 domains act in tandem and in cooperation with other SNARE proteins to regulate vesicle fusion is still under debate and will need further exploration.…”
Section: Resultssupporting
confidence: 79%
“…Given the close proximity of the lysine-rich cluster and the CBR, these results are compatible with a parallel orientation model (Fig. 6F) in which these two motifs would interact with a vesicle representing the plasma membrane, leaving the bottom face free to interact in trans with another lipid vesicle (19,(47)(48)(49)(50)(51). How these two C2 domains act in tandem and in cooperation with other SNARE proteins to regulate vesicle fusion is still under debate and will need further exploration.…”
Section: Resultssupporting
confidence: 79%
“…Noteworthy, the Ca 2ϩ binding affinity determined here is close to the concentrations of Ca 2ϩ microdomains required for the vesicle fusion process (49). For several other C2 domains it was also shown that the formation of localized pools of PIP2 plays an important role for enhancing Ca 2ϩ binding affinity (26,50). This may also be the case for the C2 domains of rabphilin-3A.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, Ca 2ϩ serves a specific structural role in allowing the C2 domain to bind anionic membranes. In addition to the Ca 2ϩ -binding site, a lysine-rich cluster within the ␤3-and ␤4-sheets of the C2 domain binds phosphatidylinositol 4,5-bisphosphate (27,(32)(33)(34)(35)(36). It is this interaction with phosphatidylinositol 4,5-bisphosphate that directs conventional PKC isozymes to the plasma membrane, which is enriched in this lipid (38 -41).…”
mentioning
confidence: 99%